PEMBAHARUAN AKSES PENDIDIKAN: Studi Persepsi Orangtua Peserta Didik terhadap Sistem Zonasi dalam Penerimaan Peserta Didik Baru (PPDB) di Kota Blitar - Sulistyo Anjarwati; Rochmat Rochmat (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2020)
This article discusses how parents' perceptions of students when responding to the zoning system in the New Student Reception System (PPDB), especially in the City of Blitar. This research is based on qualitative data obtained from the field (field research), both from primary sources: interviews and observations, as well as other secondary sources: studies on the development of PPDB studies that occur in Indonesia, both from print or electronic media. The results showed that parents of students still felt that the zoning system in PPDB did not provide free space in accessing education as desired. The government has changed the old pattern of society into a new, more complex arrangement in terms of educational facilities. In addition to having effectiveness in changing people's perceptions of the differences between favorite and non-favorite schools, this system is conceptually good, but it is not yet effective enough to equalize the quality of education, so there is still a need for deep integrative studies, strategic efforts between educational institutions and relevant agencies. This step can be done through optimizing the socialization of the PPDB zoning system to the community that promotes openness and is in favor of the people's aspirations.